Front Cover: Insights into the Effect of the Adsorption Preference of Additives on the Anisotropic Growth of ZSM‐5 Zeolite (Chem. Eur. J. 58/2022). Issue 58 (19th October 2022) - Shi, Jing; Du, Yujue; He, Wanren; Zhao, Guoliang; Qin, Yucai; Song, Lijuan; Hu, Jun; Guan, Yong; Zhu, Junfa; Wang, Chuanming; Teng, Jiawei; Xie, Zaiku
Abstract : Little sparks burst into mighty flame ! The cover picture shows the effect of eight organic additives on the anisotropic growth of a classical ZSM‐5 zeolite at the molecular level. The morphologies, from sphere‐like via plate‐like to noodle‐like, can be obtained by the introduction of additives with increasing adsorption strength difference on three typical surfaces. More information can be found in the Research Article by C. Wang, J. Teng, Z. Xie and co‐workers (DOI: 10.1002/chem.202201781 ).